Entrepreneurship, Effective Sales Management and Forex for Tourism and Hospitality - Murugan, Annamalai, 1969- (Trinity Press, an imprint of Laxmi Publications Pvt Ltd, 2019)
"Entrepreneurship, Effective Sales Management and Forex for Tourism and Hospitality explains the aspects that should be considered when starting a new business venture, both in terms of the theoretical framework and practical examples. It covers types of entrepreneurship; identifying and implementing business opportunities; planning and managing the business in terms of finance, marketing and operations, and business plans. Managing growth in a business, ethical and social responsibilities, and legal aspects affecting ventures are also explained. There are two categories of entrepreneurship textbooks: (1) those that are used in introduction to entrepreneurship courses and provide a brief introduction to each of the major steps in the entrepreneurial process and (2) those that focus on niche areas within entrepreneurship and are used in advanced classes. The edition of this book is first category and continues to provide management students and entrepreneurs an insight into the nuances of starting and managing a business in India. Entrepreneurship is an outlook of life which has been acknowledged as one of the essential factors that determines growth of any industry. It is a tremendous force that can have a big impact on growth, recovery and societal progress by fuelling innovations, employment generations and social empowerments. Today's skill and knowledge based Indian economy is a fertile ground for entrepreneurs. It is rightly believed that India has an extraordinary talent pool with virtually limitless potential to become entrepreneurs. It is the ability to see opportunities in our environment and exploit them to create something new and better. This book will serve as a textbook for various courses like B.Com., B.B.M., M.T.A., M.B.A., etc., of all Indian universities. KEY FEATURES Coverage of course requirements in crisp and lucid manner Step wise explanations for clearer understanding and practice. Overview of key concepts, exploring relevant issues."--